The Moslema entrepreneurship and product innovation: Its impact on market orientation and performance of small and medium enterprises - Ade Octavia; Dahmiri Dahmiri; Panggita Wijaya; Yayuk Sriayudha (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
The development of entrepreneurship in a country is inseparable from the participation and role of women.Women's participation as an entrepreneur has increased quite sharply over the past decade and it turns out that the role is increasingly significant not only in developed countries but also in developing countries.This research aims to analyze the influence of Moslema entrepreneur and product innovation on market orientation and performance of SMEs.The research design uses a sample survey design with a quantitative approach. The population of this study is Islamic women entrepreneur who engaged as business owner called Moslema entrepreneur. Total sample amount of 86 people.The data analysis tool uses pathways analysis. The results showed that there is a significant influence between product innovation on performance and entrepreneurship on performance. Meanwhile this study stated that market orientation variables do not act as intervening variables. Thus, Moslema entrepreneurship needs to improve to increase performance. Moslema entrepreneurs must always innovate in marketing their products to consumers. Moreover, this research is expected to contribute empirically to strategic decision-making by SMEs.